Types of tax in crowdfunding platforms: A comparative doctrinal and policy analysis - Abdelaziz, Salaheddine (The International tax journal, 2025)
This article develops a comprehensive taxonomy of taxes arising in crowdfunding—at the level of platform operators, project creators, and investors/lenders—and applies it comparatively to the United States, the European Union/United Kingdom, Australia, and Canada. Using a doctrinal comparative method grounded in primary legal sources (statutes, directives, administrative guidance) and selective secondary literature, we show that crowdfunding transactions are governed not by a bespoke fiscal regime but by the edge conditions of existing rules. Particular emphasis is placed on European Union value‑added tax (VAT) chargeability at prepayment for identified supplies, the ‘deemed‑supplier’ mechanism for some platform‑facilitated sales, the expansion of platform reporting (e.g., DAC7/OECD MRDP), and the evolution of U.S. information reporting by third‑party settlement organizations (Form 1099‑K). We formalize timing and characterization tests across donation, reward/pre‑sale, lending (peer‑to‑peer), and equity models; demonstrate their implications through cross‑border case studies; and translate doctrine into operational heuristics and policy recommendations. Illustrative tables and figures synthesize jurisdictional differences, reporting pipelines, and the decision nodes that determine indirect tax liability. The analysis builds on an earlier manuscript and provides a rigorous, practitioner‑oriented framework for embedding compliance into platform and campaign design.